The impact of the COVID-19 pandemic on the future pensions of the Peruvian pension system - Javier Olivera; Jose A. Valderrama (Inter-American Development Bank (IDB), 2022)
We study the effects of the COVID-19 pandemic and the pension policy response on the private and public pension systems of Peru. We find that the policies allowing early withdrawals from the private pension balances imply a significant reduction in expected pension wealth by about 40 people, yet there are important heterogeneous effects: the losses are larger for males, for affiliates at the bottom of the distribution of income or pension wealth, and for older people as they have less time to rebuild their pension pots. We detect that the excess of mortality due to the pandemic will reduce the actuarial net liability of the public pension system by about 2.4 percent, even after accounting for new survival pensions and a drop in contributions. The effect is largely driven by savings due to the anticipated deaths of pensioners. Moreover, a new set of reduced pension benefits implemented in the public pension system during the pandemic could cost about 4 percent of the actuarial net reserve.
Keywords: D31; G28; H55; J14; J32; 330; COVID-19; Old-age security; Peru